The Urgency of the National Insight Test as an Instrument for Assessment of Acceptance of the Corruption Eradication Commission - Ulfah Dwi Rahmawati; Adik Sukmawati; Engine Kubota (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of this study is to describe the implementation of the National Insight Test in the acceptance of the State Civil Apparatus at the Corruption Eradication Commission and the concept of a fair and transparent National Insight Test. The National Insight Test is a material test that aims to test how good the insight and knowledge of candidates for the State Civil Apparatus are about Pancasila, the 1945 Constitution, Bhineka Tunggal Ika, the Unitary State of the Republic of Indonesia, nationalism, Indonesian language, and insight into the pillars of the state. The method used in this research is the normative legal method (juridical-normative) using normative data, the data collection technique used isLibrary Research, and legal materials are processed by Content Analysis. The National Insight Test, which was used as a condition for transferring the Corruption Eradication Commission's employment status to the State Civil Apparatus, was considered very odd, and it was estimated that there was a mastermind who manipulated the data from the results of the National Insight Test.